Gestión de la calidad universitaria: UNA visión desde la experiencia - Virginia Sánchez-Molina; Carlos Hernández-Salazar (Revista Electrónica Educare)
The objective of this paper is to contribute with the study of quality management in a Higher Education institution and in its programs. The first part addresses the concepts of quality, leadership, evaluation, self-evaluation and accreditation. Then, we present the background of and achievements in the process of developing a high-level quality management at Universidad Nacional. Finally, the elements that must make up a quality management system are proposed.